2018
DOI: 10.1101/418210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic prediction of cognitive traits in childhood and adolescence

Abstract: Recent advances in genomics are producing powerful DNA predictors of complex traits, especially cognitive abilities. Here, we leveraged summary statistics from the most recent genome-wide association studies of intelligence and educational attainment to build prediction models of general cognitive ability and educational achievement. To this end, we compared the performances of multi-trait genomic and polygenic scoring methods. In a representative UK sample of 7,026 children at age 12 and 16, we show that we c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 31 publications
5
47
0
Order By: Relevance
“…While we are unaware of any study which quantifies between-country variations in the genetic signal of social class or other vectors of shared environmental effects on educational achievement, due to the highly divergent histories of these countries we find it unlikely that social stratification-driven effects on educational attainment are associated with similar genetic variants in Hungarian, Estonian and English samples. The degree of reduction in the PGS heritability in former Warsaw Pact countries relative to Anglo-Saxon samples (9-11% in the current sample, over 10% in a larger British sample (Allegrini et al, 2019;Selzam et al, 2019) versus 6-6.5% in young Hungarians and Estonians) is consistent with the roughly 50% reduction seen in recent within-family studies Selzam et al, 2019) which by design exclude social stratification, and the remaining proportion may index true genetic effects. We note, however, that genetic nurture (a true genetic effect on the parents causing a behavioral phenotype which increases offspring educational attainment) may still contribute to PGS heritability in the latter countries .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…While we are unaware of any study which quantifies between-country variations in the genetic signal of social class or other vectors of shared environmental effects on educational achievement, due to the highly divergent histories of these countries we find it unlikely that social stratification-driven effects on educational attainment are associated with similar genetic variants in Hungarian, Estonian and English samples. The degree of reduction in the PGS heritability in former Warsaw Pact countries relative to Anglo-Saxon samples (9-11% in the current sample, over 10% in a larger British sample (Allegrini et al, 2019;Selzam et al, 2019) versus 6-6.5% in young Hungarians and Estonians) is consistent with the roughly 50% reduction seen in recent within-family studies Selzam et al, 2019) which by design exclude social stratification, and the remaining proportion may index true genetic effects. We note, however, that genetic nurture (a true genetic effect on the parents causing a behavioral phenotype which increases offspring educational attainment) may still contribute to PGS heritability in the latter countries .…”
Section: Discussionsupporting
confidence: 84%
“…Large-scale genome-wide association (GWA) studies linked specific genetic variants to educational attainment (Rietveld et al, 2013;Okbay et al, 2016;Lee et al, 2018). Polygenic scores based on GWAS results confirmed the predictive value of these genetic variants (also termed polygenic score [PGS] heritability), typically accounting for up to 10% of the phenotypic variance in educational attainment itself Allegrini et al, 2018), cognitive abilities (de Zeeuw et al, 2014;Selzam et al, 2016;Allegrini et al, 2018), social mobility (Ayorech et al, 2017) and overall socioeconomic success (Belsky et al, 2016;Belsky et al, 2018) in independent samples. However, the association between genetic variants identified by GWAS and phenotypes may be mediated or moderated by environmental variables in at least two ways.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, initial evidence suggests that currently available datasets might be able to explain up to 50% of the variance in height by using LASSO, and that a similar doubling of explained variance is also possible for cognitive phenotypes [27]. Additionally, the use of multiple related phenotypes has been demonstrated to enhance the predictive power of PS [47]; for example, the combination of educational attainment and intelligence GWAS may permit a doubling of cognitive ps 2 [48]. Finally, it has recently been suggested that enrichment of certain subcategories of functional variation (e.g., coding, conserved, regulatory, and LD-related genomic annotations) in GWAS results can be leveraged to further enhance prediction accuracy [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…We prefer to use AUC over Nagelkerke's R 2 because AUC has a desirable property of being independent of the proportion of cases in the validation sample; one definition of AUC is the probability that the score of a randomly selected case is larger than the score of a randomly selected control (Wray et al 2013). An alternative to AUC would be to use a better R 2 on the liability scale (Lee et al 2012;Allegrini et al 2019).…”
Section: Simulationsmentioning
confidence: 99%